Sistem Informasi Pelayanan Jasa Laundry Pada Rumah Laundry Kendal - Bagus Sudirman; Ahmad Ashifuddin Aqham (Lembaga Pengembangan Kinerja Dosen, 2023)
Currently it is still done manually and causes difficulties in data retrieval and income capitulation, there are several steps that can be taken to increase efficiency and accuracy in administrative management. Here are some suggestions: Management Information System (MIS) or Laundry Application: Implement a management information system or laundry-specific application that can help automate administrative processes. This application can record laundry receipt transactions, record customer data, and store income information in a more structured manner. Barcode or Unique Identification System: Use a barcode or unique identification system on each laundry receipt. This will make it easier to track and search data. Each customer or order can have a unique code or barcode that can be scanned to identify the transaction. Electronic Logging: Switch from manual logging to electronic logging. Use spreadsheet or database software to store and manage data. Make sure all laundry receipt data, including customer information and type of service, is recorded carefully. Centralized Database System: By implementing these solutions, you can optimize the laundry service administration process, reduce data search time, and increase revenue management efficiency. The aim of creating a Laundry Service Information System is to make it easier for business owners to manage customer transaction data and in preparing financial reports. The methods used in collecting data are observation, interviews and literature study, while the system development method used is R&D (Research and Development). This system was built using the PHP programming language, Boostrap, and for the database using MySQL. The results of this research are a web-based laundry service information system. This laundry service information system contains 2 access rights, namely Admin and customer. Customers can find out the status of their laundry and payments, while Admins can manage customer data, manage transactions, and view print reports